Sport dreams in a long dream series - Schredl, Michael (International journal of dream research, 2019)
Although the frequency of sport dreams has been studied, studies looking at the relationship between sport disciplines and dream content are quite rare. The present findings are based on 11,463 dreams of an academic who practiced during several years quite intensely circus arts (juggling, unicycling, and acrobatics). The overall percentage of sport dreams (6.12%) is comparable with previous findings. Circus art dreams were unique to the dreamer (not found in a large sample of student dreams) and occurred most often during the period of intense practice. One of the most intriguing questions is whether these sport dreams reflect sleep-dependent memory consolidation processes, i.e., whether dreaming about sport is related to performance improvements.